Implementasi Nilai-Nilai Ekonomi Syariah pada Pondok Pesantren Terpadu Daarul Ilmi - Mutiara Pertiwi; Sabrina Ramadhani; Kanaya Oktaviani; Muhammad Zaini El Wahyu (Jurnal Al-fatih Global Mulia, 2024)
This research aims to explain the influence of the cooperative or canteen of the Daarul Ilmi Integrated Islamic Boarding School on Sharia Economic values ​​and the influence of entrepreneurship based on Islam in accordance with Maqosyid Syariah and economic goals according to Adam Smith. The method used in this research is a qualitative descriptive method. The results of the analysis of the research data show that there is a positive or negative influence between the attitudes of the market community and the boarding school students, and this cooperative has helped a lot with the economy of the Islamic boarding school and the surrounding community, and the students at the Daarul Ilmi Integrated Islamic Boarding School.